Measuring the Impact of the COVID-19 Pandemic on Diagnostic Delay in Rare Disease - Caitlin Hampson; William Evans; Lucy McKay; Lara Menzies (European Medical Journal)
Rare diseases are individually rare but collectively common, with a combined prevalence of 3.5–5.9%. A common feature of many diseases is a substantial delay in patients receiving a correct diagnosis; this protracted path to diagnosis is termed ‘the diagnostic odyssey’. During the COVID-19 pandemic, significant concerns have emerged from both clinicians and patients regarding a disproportionate effect of the pandemic on diagnosis and management of rare disease. Such concerns prompted a study to explore this question further, the results of which are presented here. A cross-sector multi-stakeholder coalition was formed, Action for Rare Disease Empowerment (ARDEnt), with representation from patients with rare diseases and carers, patient advocacy groups, clinicians, academics, data scientists, and industry. A mixed methods approach was used to collect and collate information about the impact of the pandemic on diagnostic delay in rare disease. Currently, there is a lack of systematic recording and reporting of rare disease diagnosis in the UK, which created challenges in directly measuring diagnosis rates. Therefore, the group was dependent on a mix of data sources to reflect healthcare provided during 2020 compared with previous years. The findings were synthesised to describe the impact of the pandemic along the path to diagnosis, from the moment of first concern and engagement with health services, to the availability of definitive testing. In conclusion, evidence suggests the pandemic has exacerbated the problem of diagnostic delay for rare diseases, affecting all points on the path to diagnosis. The authors recommend three actions to help address this: optimising remote clinical consultations; enhancing the use of health informatics in rare diseases; and proactively identifying patients with undiagnosed rare diseases missed due to the pandemic. This study also highlights the need for better reporting of rare disease diagnoses, a core metric to measure the impact of health system changes that may be put into place to address the priorities of The UK Rare Diseases Framework, also published this year.